Hard Radiation Detection from the Selenophosphate Pb2P2Se6. (2nd July 2015) - Wang, Peng L.; Liu, Zhifu; Chen, Pice; Peters, John A.; Tan, Gangjian; Im, Jino; Lin, Wenwen; Freeman, Arthur J.; Wessels, Bruce W.; Kanatzidis, Mercouri G.
Abstract : The heavy metal selenophosphate, Pb2 P2 Se6, is a promising new material for cost‐effective X‐ray/γ‐ray detection. Crystal boules of Pb2 P2 Se6 up to 25 mm in length and 15 mm in diameter are grown by a vertical Bridgman method. They are cut and processed into size‐appropriate wafers for physical, photo‐transport property studies, as well as γ‐ray detector testing. The material is a semiconductor with an indirect bandgap of 1.88 eV and has electrical resistivity in the range of 1 × 10 10 Ω cm. Pb2 P2 Se6 single crystal samples display a significant photoconductivity response to optical, X‐ray, and γ‐ray radiation. When tested with a 57 Co γ‐ray source, Pb2 P2 Se6 crystals show spectroscopic response and several generated pulse height spectra resolving the 122.1 and 136.5 keV 57 Co radiation. The mobility–lifetime product of Pb2 P2 Se6 is estimated to be ≈3.5 × 10 −5 cm 2 V −1 for electron carriers. The Pb2 P2 Se6 compound melts congruently at 812 °C and has robust chemical/physical properties that promise low cost bulk production and detector development. Abstract : Wide bandgap selenophosphate Pb2 P2 Se6 is identified as a cost‐effective X‐ray and γ‐ray detector material. The crystal growth of Pb2 P2 Se6 and characterizations in terms of its optical, electrical, thermal, and mechanical properties are reported. A Pb2 P2 Se6 single crystal detector is able to resolve 57 Co radiation.